Financial intermediation, capital composition and income stagnation: The case of Europe - Samatas, Andreas; Makrominas, Michalis; Moro, Andrea (Elsevier, 2019)
We look into the role of financial intermediation in inducing the European financial crisis of 2008 by exploring the effects of overall lending, and the allocation of credit to specific categories of borrowers, namely households vs. firms. We find that for the EU26 during the period 1995–2008, excessive household leverage through mortgage lending exerted a “crowding-out” effect on availability of credit to support innovation and productive investment. The crowding out effect ultimately translated into a GDP growth that was decoupled from real household income. In this article we explain that shifting credit towards mortgages and away from corporate projects is consistent with rational behaviour based on historical trends aimed at minimizing short-term risk for each individual bank. Nevertheless, as a whole, the sum of individual risk-reducing attitudes generated a long-term systemic risk.
Keywords: Financial-intermediation; Fixed-capital-formation; Economic-growth